Telemedicine applications in pediatric emergency surgery and trauma: a systematic review of diagnostic accuracy and clinical effectiveness - Amani N. Alansari (19743643) (2025)
Aim This review examines the effectiveness, implementation factors, and outcomes of telemedicine applications in managing surgical emergencies and trauma in pediatric patients. Methods We conducted a systematic review following PRISMA guidelines. Comprehensive searches were performed across four major databases (PubMed, Scopus, Web of Science, and Cochrane Library) from inception to January 2025. Studies that investigate telemedicine interventions in pediatric (ages 0–18) emergency surgery and trauma settings were included. Results Eleven studies met inclusion criteria, comprising 6 retrospective cohorts, 3 cross-sectional studies, 1 prospective cohort, and 1 case series. Diagnostic accuracy was consistently high across applications (sensitivity: 93.8–100%; specificity: 82.6–99.7%). Telemedicine demonstrated effectiveness in preventing unnecessary transfers, with one study reporting 16 prevented transfers. Remote-guided procedures showed comparable accuracy to in-person assessment, particularly in point-of-care ultrasound (sensitivity: 93.8%, specificity: 99.7%). High satisfaction rates were reported among families and healthcare providers. Conclusions This review highlights the potential of telemedicine in pediatric emergency surgery and trauma care, particularly in enhancing access to specialized care and maintaining diagnostic accuracy. However, the generalizability of findings remains limited due to variations in study methodologies. Future research should emphasize prospective designs and economic evaluations to clarify the cost–benefit ratio of implementation. Establishing standardized protocols and enhancing provider training will be essential for the effective and sustainable integration of telemedicine into pediatric trauma systems. Other Information Published in: Pediatric Surgery International License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00383-025-06023-9